Avaliação de fontes sólidas de carbono inorgânico na suplementação do cultivo de microlagas em efluente anaeróbio - Dassoler, Aline Figueredo (2019)
The use of solid sources of inorganic carbon (NaHCO3 and CaCO3) as CO2 supplementation was evaluated in the growth of Chlorella sp. with effluent from the anaerobic treatment of sewage. The correction of the pH through CO2 bubbling in CaCO3 treatments avoided the negative effects generated by the increase in pH with the addition of the reagent, and contributed to the CO2 fixation in the medium – increasing the amount of available inorganic carbon up to 201%. The maximum growth rate and productivity were achieved using 2.0 g/L of NaHCO3 (0.53 d-1 and 66.1 mg.L-1 .d-1 ) and 1.19 g/L of CaCO3 (0.54 d-1 and 67.5 mg.L-1 .d-1 ). The use of solid sources of inorganic carbon increased the growth rates and biomass productivities of Chlorella sp. cultures by a factor of 2.0 and 1.8, respectively, when compared to treatments without additional carbon sources. Additionally, an increase in the volatile solids content of the biomass was noted, which consisted in 21% for NaHCO3 and 20% for CaCO3. On the other hand, treatments that received no solid carbon sources but had aeration 12 h/day displayed similar results when compared to the solid carbon treatments, regarding growth rate, maximum biomass concentration and percentage of volatile solids in the biomass. Nevertheless, the microalgae consortium did not present significant increase in growth for any of the forms of supplementation applied. The use of solid sources of inorganic carbon in the form of bicarbonates can be an alternative to gaseous CO2 supplementation in microalgae cultures, since the carbon in this form is stable in liquid medium, reducing losses to the atmosphere. Due to the increase in pH, the use of CaCO3 is only viable in case the correction of the initial pH is performed. In this case, the use of CO2 bubbling is advantageous since it allows its fixation in the alkaline medium. Further studies with microalgae consortia using different concentrations and combinations of carbon sources may bring new alternatives for the optimization of biomass production with effluents from sewage treatment and improve the efficient use of CO2 in microalgae cultures